2013
DOI: 10.2478/s11686-013-0160-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses of B. malayi thioredoxin (TRX) and venom allergen homologue (VAH) chimeric multiple antigen for lymphatic filariasis

Abstract: Although multiple vaccine strategy for lymphatic filariasis has provided tremendous hope, the choice of antigens used in combination has determined its success in the previous studies. Multiple antigens comprising key vaccine candidates from different life cycle stages would provide a promising strategy if the antigenic combination is chosen by careful screening. In order to analyze one such combination, we have used a chimeric construct carrying the well studied B. malayi antigens thioredoxin (BmTRX) and veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Given its critical role for survival of the parasite in the host, TPX-2 is a potential target for vaccine development. Our group and others ( 24 , 27 , 28 , 40 42 ) have previously reported the vaccine potential of TPX. Studies showed that r Bm TRX could confer 62% protection against B. malayi challenge in Mastomys model ( 43 ) and 43–69.5% protection in mouse and jird models ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Given its critical role for survival of the parasite in the host, TPX-2 is a potential target for vaccine development. Our group and others ( 24 , 27 , 28 , 40 42 ) have previously reported the vaccine potential of TPX. Studies showed that r Bm TRX could confer 62% protection against B. malayi challenge in Mastomys model ( 43 ) and 43–69.5% protection in mouse and jird models ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 76%
“…Thioredoxin peroxidase (TPX-2) is a highly immunogenic protein within the total secretome of B. malayi ( 37 39 ). Several groups including ours have reported the vaccine potential of TPX-2 previously ( 24 , 27 , 28 , 40 42 ). In fact, one of our studies showed that a trivalent fusion protein rBm HAX (HSP12.6 + ALT-2 + TPX-2) vaccine conferred 67.5% protection in the mouse model ( 30 ).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our laboratory and others have identified and characterized several potential candidate vaccine antigens of LF and evaluated their vaccine potential in rodent models (Denham, 1980; Dissanayake et al, 1995; Gregory et al, 1997; Anand et al, 2008, 2011; Gnanasekar et al, 2008; Vedi et al, 2008; Veerapathran et al, 2009; Kalyanasundaram and Balumuri, 2011; Babayan et al, 2012; Dakshinamoorthy et al, 2012; Anugraha et al, 2013; Dakshinamoorthy et al, 2013a; Gomase et al, 2013; Arumugam et al, 2014; Gupta et al, 2016). Among the various antigens that we characterized, four antigens, abundant larval transcript-2 (ALT-2) (Anand et al, 2008; Kalyanasundaram and Balumuri, 2011; Madhumathi et al, 2017), heat shock protein (HSP) 12.6 (Dakshinamoorthy et al, 2012), thioredoxin peroxidase-2 (TPX-2) (Anand et al, 2008; Anugraha et al, 2013) and tetraspanin large extracellular loop (TSP-LEL) (Gnanasekar et al, 2008; Dakshinamoorthy et al, 2013a) gave excellent protection in rodent models. Subsequently, we showed that combining three of these antigens as a multivalent fusion protein, rBmHAT (recombinant B. malayi HSP12.6, ALT-2 and TSP-LEL) gave close to sterile immunity in mouse and jird models (Dakshinamoorthy and Kalyanasundaram, 2013; Dakshinamoorthy et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%